Teacher Autonomy Support: Does it Hinder Motivation among Thai Students? (Malaysian Journal of Learning and Instruction, 2014)
Purpose â€“ This article examined the relevance of teacher autonomy support [TAS] among Thai students. It is based on a study conducted to compare the effects of TAS on motivation among Thai students. The issue of motivation among Asian students has invited controversy as few cross-cultural relativists have claimed that Asian students get motivated when teachers use controlling strategies. Methodology â€“ The study collected data through a quasiexperimental study with an appended ABA withdrawal design. The subjects were 105 Thai students who completed self-reported questionnaires that assessed perceived autonomy support, intrinsic motivation and self-regulation, before, after and on withdrawal of experiment intervention. Findings â€“ MANOVA results revealed that students in the experimental group who were in the autonomy supportive teachinglearning environment reported greater interest, effort, relatedness and integrated regulation compared to the control group taught using a traditional approach. Furthermore, students in the experimental group experienced less pressure and reported less external regulation compared to the control group. Significance â€“ The findings support the claim in Self-determination theory (SDT) that autonomy is not a culturally bound value, and is a pedagogical concept equally relevant to Thai students as it facilitates motivation. The fi ndings will encourage Thai educators to adopt autonomy as a pedagogical concept that will help facilitate motivation among their students.